Monitoring Korosi Discharge Conveyor E pada Tambang Batubara PT GHI di Kabupaten Kotabaru Provinsi Kalimantan Selatan - Rizal Andriansyah; Elfida Moralista; Zaenal (Bandung Conference Series: Mining Engineering, 2023)
Abstract. Conveyor is a mechanical conveyance used for the coal removal process. The conveyor structure is generally made of carbon steel which is prone to corrosion when reacting with the environment. The corrosion that occurs can lead to a reduction in the thickness of the conveyor structure. Therefore, monitoring and corrosion control are needed, so as to slow down the corrosion rate and reach the design life. The purpose of this research is to determine the type of corrosion that occurs, the corrosion control methods used, Corrosion rate, and Remaining service life.In this study using the research methodology of measuring the thickness reduction of the conveyor structure. The thickness measurement of the conveyance was carried out using the Ultrasonic Gauge TT130 tool on a 95-meter-long conveyor structure divided into 3 segments with 25 test points. The data obtained include nominal thickness, actual thickness, design life of 15 years and service life of 5 years, used to calculate Thickness Required, Corrosion rate, and Remaining service life. The environmental conditions of the study area in a period of 5 years from 2015 to 2019 had an average rainfall of 197.98 mm / year, an average air temperature of 26.91 °C, and an average humidity of 83.62%. Corrosion that occurs in the conveyor structure is evenly corrosion and the corrosion control method applied is a coating with a three-layer system, namely primer coating using Seaguard 5000, intermediate coating using Sherglass FF, and top coating using Aliphatic arcylic modified polyurethane. The corrosion rate that occurs in the conveyor structure ranges from 0.1880-0.3300 mm / year, so based on the relative corrosive resistance of steel is included in the "good" category. The service life of the conveyor structure is 9.43-11.35 years. Thus, 40% of the 25 test points are predicted to not be able to reach the design life, which is 15 years. Abstrak. Conveyor merupakan alat angkut mekanis yang digunakan untuk proses pemindahan batubara. Struktur conveyor pada umumnya berbahan dasar baja karbon yang rentan mengalami korosi apabila bereaksi dengan lingkungan. Korosi yang terjadi dapat menyebabkan pengurangan ketebalan pada struktur conveyor. Oleh karena itu diperlukan monitoring dan pengendalian korosi, sehingga dapat memperlambat laju korosi serta mencapai umur desain. Tujuan dilakukannya penelitian ini untuk mengetahui jenis korosi yang terjadi, metode pengendalian korosi yang digunakan, Corrosion rate, dan Remaining service life.. Pada penelitian ini menggunakan metodologi penelitian pengukuran pengurangan ketebalan struktur conveyor. Pengukuran ketebalan dilakukan menggunakan alat Ultrasonic Gauge TT130 pada struktur conveyor sepanjang 95 meter yang terbagi ke dalam 3 segmen dengan 25 test point. Data yang diperoleh meliputi tebal nominal, tebal aktual, umur desain 15 tahun dan umur pakai 5 tahun, data tersebut kemudian diolah untuk mengetahui Thickness Required, Corrosion rate, dan Remaining service life. Kondisi lingkungan daerah penelitian dalam kurun waktu 5 tahun yang terhitung sejak tahun 2015 sampai tahun 2019 memiliki curah hujan rata-rata sebesar 197,98 mm/tahun, temperatur udara rata-rata 26,91°C, dan kelembapan udara rata-rata 83,62%. Korosi yang terjadi pada struktur conveyor adalah korosi merata dan metode pengendalian korosi yang diaplikasikan adalah coating dengan sistem three layer yaitu primer coating dengan menggunakan Seaguard 5000, intermediate coating menggunakan Sherglass FF, dan top coating dengan menggunakan Aliphatic arcylic modified polyurethane. Laju korosi yang terjadi pada struktur conveyor berkisar 0,1880-0,3300 mm/tahun, sehingga berdasarkan ketahanan korosif relatif baja termasuk ke dalam kategori “good”. Umur pakai struktur conveyor adalah 9,43-11,35 tahun. Dengan demikian terdapat 40% dari 25 test point yang diprediksi tidak dapat mencapai umur desain, yakni 15 tahun.